Effects of heat treatment on structure and thermal diffusivities of SiO₂-A1₂O₃-Na₂O-CaO-CaF₂ glass-ceramics from waste materials - Loy, Chee Wah (2012)
Recycling waste materials into dental application is a developing field of study. Soda-lime-silica (SLS) glass and clamshell (CS) were used in this research to make dental glass-ceramics. The manufacture of glass-ceramics by using waste materials for dental industries can reduce a large amount of solid wastes produced daily. This research was focused on the phase transformations and thermal diffusivities of SiO2- Na2O-Al2O3-CaO-CaF2 glass-ceramics which made by different weight ratio of CS and CaF2 powders. This research is important to obtain an optimum composition and heat treatment temperature to improve the properties of glass-ceramic for dental applications. Two series of SiO2-Na2O-Al2O3-CaO-CaF2 mixture samples (SM1- SM4) and glass samples (SG1-SG4) were produced. The raw materials used in this research were SLS glasses, α-alumina (Al2O3) powder, CS and calcium fluoride (CaF2) powder. Both SLS glasses and CS were collected from waste products in food industries. The weight formula of the samples were (SLS)0.4 (Al2O3)0.3 (CS)0.3-x (CaF2)x , where x = 0, 0.1, 0.2 and 0.3. The SM1-SM4 were produced by mixing raw materials according to their weight ratio and followed by pressing them into pellet form. Heat treatments at 500-1200 ºC for 3 hours were carried out on these pellets to obtain crystalline phases. XRD, FTIR, TGA, DTA, FESEM, and thermal diffusivity tests were carried out on SM1-SM4. The SG1-SG4 were produced by rapid cooling of molten mixture powders which based on their weight ratio. The glasses obtained were ground into powder form and followed by pressed them into pellet form. Heat treatments at 500-1300 ºC for 3 hours were carried out on these pellets to obtain crystalline phases. The crystallized SG1-SG4 glasses after being heat treated were called as glass-ceramics. XRD, FTIR, DTA, FESEM, and thermal diffusivity tests were also carried out on SG1-SG4. The result shows that all the SM1-SM4 and SG1-SG4 consists of nepheline and gehlenite phases after heat treatment at high temperature. The nepheline phase is an important phase in various dental materials, especially for dental crown. The nepheline phase at lowest heat treatment temperature was found in SG3 at 800 ºC. The glass transition and crystallization temperatures of SG3 were 680 and 872 ºC respectively.